Attaining Financial Efficiency Through Funds Utilization the Bankers’ Perspective: A Comparative Study Murabaha Funds of Islamic Banks Vis-à-Vis Loan Amount of Conventional Banks - Ud-Din, Imam; Shujat Saleem, Muhammad (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2015)
In reply to the argument made by the non-believers of Makkah “Sale is similar to riba”, Almighty Allah ordered “Sale is permissible while riba is impermissible”. The main intent of the study was to clarify the fallacy prevailing among the Muslims that in practical terms the product of Murabaha which is being offered by the Islamic banks is similar to that of conventional interest-based business loan3. However, specific objective was to ascertain the degree of financial efficiency on the basis of fund/loan utilization for intended purpose of Murabaha financing vis-à-vis conventional interest-based business loan. The study employed survey strategy to collect primary data through structured close ended questionnaires from the sample of 98 Murabaha officers and 178 loan officers out of the whole population of 5 Islamic and 10 conventional banks respectively. Quantitative and qualitative techniques were used to analyze the data and the same is tabulated by use of frequency tables. The study found that the financial efficiency of Murabaha financing is more than that of conventional interest-based business loan by 28% as Murabaha funds of Islamic banks are utilized for its intended purpose to the extent of 97% on average, compared to 69% of business loan offered by conventional banks.